Inteligencia emocional y rendimiento académico en estudiantes del V ciclo primaria de una institución educativa de Ventanilla - Callao - Manrique Yzaguirre, Francisco Abel (2012)
This descriptive correlational research aimed to describe and establish the relationship between emotional intelligence and academic achievement in the areas of math and comunication of the of fifel cycle primary students from a public school in Ventanilla, Callao. The sample were 145 students of 5th and 6th grades. The Bar On Emtional Intelligence ICE NA inventory, adapted and applied in Perú by Ugarriza Ch. And Pajares Del A. (2003) (Complete form) was used. The results showed that there is a weak positive relationship betwen total emotional intelligence and academic achievement in math and comunication as well as in the enterpersonal dimension. And found no significant relationship in the other dimensions. It was concluded that students with high emotional skills not always have better academic achievement.